The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1371/journal.pone.0209941
|View full text |Cite
|
Sign up to set email alerts
|

A genetically engineered microRNA-34a prodrug demonstrates anti-tumor activity in a canine model of osteosarcoma

Abstract: Osteosarcoma (OSA) represents the most common primary bone tumor in humans and pet dogs. Little progress has been made with regard to viable treatment options in the past three decades and patients presenting with metastatic disease continue to have a poor prognosis. Recent mouse studies have suggested that microRNA-34a (miR-34a) may have anti-tumor activities in human OSA models. Due to the conservation of microRNA across species, we hypothesized that a bioengineered miR-34a prodrug (tRNA/miR-34a) would have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…With such novel bioengineered miRNA agents produced cost effectively and on a large scale, extensive functional studies have been conducted and the results showed rather a modest change in the PK of major CYP probe drugs in mouse models 134 . Further studies have demonstrated the utility of miRNAs as therapeutics or sensitizing agents for the treatment of human diseases in various animal models 133 , 135, 136, 137, 138, 139.…”
Section: Determinants Of Pkmentioning
confidence: 99%
“…With such novel bioengineered miRNA agents produced cost effectively and on a large scale, extensive functional studies have been conducted and the results showed rather a modest change in the PK of major CYP probe drugs in mouse models 134 . Further studies have demonstrated the utility of miRNAs as therapeutics or sensitizing agents for the treatment of human diseases in various animal models 133 , 135, 136, 137, 138, 139.…”
Section: Determinants Of Pkmentioning
confidence: 99%
“…Stable overexpression of miR-34a in canine OS cell lines also reduced the expression of angiogenic factors such as VEGFA (Vascular Endothelial Growth Factor) with a concomitant consequent decrease in cell invasion and migration [ 47 ]. Furthermore, lower expression of mi-34a in tumor and plasma has also been associated with poor prognosis and chemo resistance, and, recently, a new bioengineered tRNA/miR-34a prodrug demonstrated important antitumor activity in a canine model of OS [ 4 ].…”
Section: Mirna In Canine and Human Osteosarcoma: Comparative Featumentioning
confidence: 99%
“…The comparison of the expression of microRNAs among neoplastic and normal cells has further established their role in the oncogenesis of many tumors by means of interaction and promotion mechanisms on target genes [ 3 ]. Moreover, the miRNAs alterations often correlate with a more aggressive tumor biological behavior, making these molecules potential prognostic and therapeutic targets [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…BERAs carry no or minimal posttranscriptional modifications, are biologically active in regulating target gene expression and cellular processes, and are well tolerated in animal models (Alegre et al 2018;Chen et al 2015;Ho et al 2018;Jian et al 2017;Jilek et al 2017;Jilek et al 2019;Li et al 2015;Li et al 2018;Tu et al 2019;Umeh-Garcia et al 2019;Xu et al 2019;Zhang et al 2018;Zhao et al 2016;Zhao et al 2015), resembling cellular RNAi mechanisms (Fig. 3).…”
Section: Hybrid Trna/pre-mirna Carriermentioning
confidence: 99%